A Single‐Electron Transistor Made of a 3D Topological Insulator Nanoplate. Issue 42 (6th September 2019) - Jing, Yumei; Huang, Shaoyun; Wu, Jinxiong; Meng, Mengmeng; Li, Xiaobo; Zhou, Yu; Peng, Hailin; Xu, Hongqi
Abstract: Quantum confined devices of 3D topological insulators are proposed to be promising and of great importance for studies of confined topological states and for applications in low‐energy‐dissipative spintronics and quantum information processing. The absence of energy gap on the topological insulator surface limits the experimental realization of a quantum confined system in 3D topological insulators. Here, the successful realization of single‐electron transistor devices in Bi2 Te3 nanoplates using state‐of‐the‐art nanofabrication techniques is reported. Each device consists of a confined central island, two narrow constrictions that connect the central island to the source and drain, and surrounding gates. Low‐temperature transport measurements demonstrate that the two narrow constrictions function as tunneling junctions and the device shows well‐defined Coulomb current oscillations and Coulomb‐diamond‐shaped charge‐stability diagrams. This work provides a controllable and reproducible way to form quantum confined systems in 3D topological insulators, which should greatly stimulate research toward confined topological states, low‐energy‐dissipative devices, and quantum information processing. Abstract : A topological insulator single‐electron transistor device is fabricated using state‐of‐the‐art nanofabrication techniques, and the device shows well‐defined Coulomb current oscillations and Coulomb‐diamond‐shaped charge stability diagrams.